ESP teaching practices: Fostering cultural bonding - Tavella, Gabriela Nelly; Fernández, Silvia Carina (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
This article aims to reflect upon the importance of promoting teaching practices that foster cultural bonding through the development of communicative skills when working with future tour guides in an ESP context. Our reflection will be supported by the practice of Content and Language Integrated Learning (CLIL), and the ideas developed by the postmethod pedagogy. We will analyse our role as ESP teachers in the 21st century in our own particular context, and how this role is constantly changing .We will also consider how the theoretical principles mentioned above influence our teaching practices. Our practice will be described, analysed and evaluated so that it might be replicated in other contexts.